2023
DOI: 10.3389/fendo.2023.1189574
|View full text |Cite
|
Sign up to set email alerts
|

Association between remnant cholesterol and chronic kidney disease in Chinese hypertensive patients

Abstract: BackgroundRemnant cholesterol (RC) and chronic kidney disease (CKD) have not been definitively linked in individuals with different characteristics. This study aims to investigate the relationship between serum RC level and CKD and examine possible effect modifiers in Chinese patients with hypertension.MethodsOur study is based on the Chinese H-type Hypertension Project, which is an observational registry study conducted in real-world settings. The outcome was CKD, defined as an estimated glomerular filtration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…In addition, prospective cohort studies also found that an increase in RC was associated with the progression of renal impairment, suggesting that RC can be used as a monitoring indicator for the development of CKD [ 16 , 19 ]. Recent studies have indicated a significant association between elevated RC levels and CKD in populations with cardiovascular risk factors such as hypertension and diabetes [ 18 , 20 , 21 ]. However, in the Chronic Renal Insufficiency Cohort study, TGs, TC, LDL-C, and HDL-C levels were not independently associated with the progression of kidney function decline [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, prospective cohort studies also found that an increase in RC was associated with the progression of renal impairment, suggesting that RC can be used as a monitoring indicator for the development of CKD [ 16 , 19 ]. Recent studies have indicated a significant association between elevated RC levels and CKD in populations with cardiovascular risk factors such as hypertension and diabetes [ 18 , 20 , 21 ]. However, in the Chronic Renal Insufficiency Cohort study, TGs, TC, LDL-C, and HDL-C levels were not independently associated with the progression of kidney function decline [ 5 ].…”
Section: Discussionmentioning
confidence: 99%